Conceptual change of an occupation: Transformation of teaching in Turkey in neoliberal times (1980-2013) - Ertem, Ece Cihan. (Thesis (Ph.D.) - Bogazici University. Atatürk Institute for Modern Turkish History, 2018., 2018)
Primary school teachers in Turkey comprised an influential group in Turkish society in the twenty-first century since they are a large occupational group among state workers. Moreover, their occupation touches the heart of everyday life due to the responsibilities it entails. However, the prestige of such an influential occupation seems declining in Turkey and in some other countries, as well. Although this decline appears to be a widespread global phenomenon in both developed and developing countries, the reasons, results, and processes of this decline in Turkey have local characteristics. This dissertation portrays the transformation and conceptual change in primary school teaching in the period from 1980 to 2013 by appointing the September 1980 coup as a turning point. The dissertation focuses on the effects of the state interventions, and the reflections in society and in the attitudes of parents and teachers themselves of the transformation of the occupation. Furthermore, the study examines abstract concepts related to the images of primary school teachers in their portrayal in Turkish literature. It peeks into classrooms and describes the actual occupational practice of primary school teachers. Last, the study scrutinizes gender roles in Turkish primary schools and the feminization of the occupation. This dissertation addresses these subjects using the data from a comprehensive face-to-face survey conducted throughout Turkey as well as in-depth interviews that were designed to convey the exact phrases of teachers and recover their voices which have been hidden among legal decrees, books, occupational journals, and documents.
Keywords: Primary school teachers -- Turkey.; Neoliberalism -- Turkey.